The effect of different Paricalcitol doses on the spleen zones in BALB/c mice infected with the H1N1 subtype influenza virus - Sataieva, Tatiana; Malygina, Veronika; Komissarova, Veronika (Edelweiss Applied Science and Technology, 2025)
Recent studies have revealed that vitamin D and its synthetic analogues possess protective antioxidant and anti-inflammatory effects on experimental models of ischemia and autoimmune conditions across various organs. However, limited information is available regarding their impact on the spleen during severe viral infections. The primary aim of this research was to investigate the effects of different doses of Paricalcitol on spleen zones in BALB/c mice infected with the influenza virus subtype A/WSN/1/33 (H1N1). The study involved male BALB/c mice, weighing between 16 and 18 grams and aged 4 to 6 weeks, which showed no external pathological signs. The experiments were conducted in two stages: first, to assess the impact of various doses of intraperitoneally administered Paricalcitol on histological changes in the murine spleen; second, to evaluate the effect of a 50 ng/mouse dose of Paricalcitol during influenza infection on spleen histology. The findings demonstrated that infection with the highly pathogenic influenza virus A/WSN/1/33 (H1N1) initiated the destruction of lymphatic nodules within the spleen. Notably, the average area of lymph nodes in animals receiving a high dose of 100 ng/mouse was reduced by 1.7 times compared to the control group. Based on these results, a dose of 50 ng/mouse of Paricalcitol was selected for further experiments involving viral infection. The intraperitoneal administration of 50 ng/mouse of Paricalcitol on the 10th day of infection significantly increased the average area of the marginal zone of B-lymphocyte maturation compared to the group that did not receive the drug, indicating a potential protective effect on spleen histology during influenza infection.